Case series: Pleural effusion caused by urinary ultrafiltrate in two cats without evidence of urinary obstruction, trauma, or simultaneous perinephric pseudocysts - Griffin, Maureen A.; Steffey, Michele A.; Phillips, Kathryn L.; Mayhew, Philipp D.; Woolard, Kevin D.; Della Maggiore, Ann (Frontiers in Veterinary Science, 2022)
Objectives: To describe the diagnostic techniques, surgical treatments, and outcomes of two cats with recurrent pleural transudate caused by urinary ultrafiltrate. Animals: Two cats without evidence of trauma, urinary tract obstruction, or concurrent perinephric pseudocysts that were evaluated and treated for recurrent pleural transudate caused by urinary ultrafiltrate. Study design: Short case series Methods: Multiphase contrast CT scan revealed leakage of contrast media from the kidneys bilaterally into the retroperitoneal spaces in both cats. Renal scintigraphy performed in one cat revealed progressive accumulation of 99mTc diethylenetriamine penta-acetic acid (Tc-DTPA) in the pleural space. Exploratory laparotomy localized the leakage of fluid to renal capsular defects bilaterally in both cats. The retroperitoneum was incised bilaterally to promote fluid drainage into the peritoneum, and nephropexies were performed. Results: One cat had long-term survival with recurrent, though decreasing volumes of, pleural effusion. The second cat was euthanized 16 days postoperatively for progressive renal disease. Conclusion: The diagnosis of spontaneous urinary ultrafiltrate accumulation in the pleural space of cats without evidence of trauma, urinary tract obstruction, or concurrent perinephric pseudocysts has not previously been reported. The surgical correction described reduced but did not completely eliminate the rate of pleural effusion accumulation.